Nilai Pendidikan Karakter Motif Batik Dewa Ruci Karya Sapuan Ditinjau dari Perspektif Thomas Lickona - Dian Triwulandari (Mahesa Research Center, 2021)
Dewa Ruci's Batik motif is the work of Sapuan a Junior High School (SMP) teacher from Pekalongan. Dewa Ruci is a unique batik work that represents the life story of the journey of Bima, a puppet character. The story of Bima's life journey visualized through this motif brings the value of character education which is full of goodness values. This research will examine the value of character education contained in the Batik Dewa Ruci motif in terms of the perspective of character education Thomas Lickona. The method used in this study is a qualitative descriptive method, using interview data with the creator of the batik to see the intrinsic motivation of the work, observations of the batik, and supported by library data. Data analysis uses a hermeneutic approach, which is interpreting the expressions that appear in the visuals of the batik. The results of the study show that the Batik Dewa Ruci by Sapuan contains the character values of Thomas Lickona's kindness, It is hoped that this research can inspire educators and artists, to be able to insert value of character education into works of art, and for readers to be able to understand the philosophical meaning of Dewa Ruci's batik.